2017
DOI: 10.1371/journal.pone.0182001
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of the digestive system in the crinoid Himerometra robustipinna occurs by transdifferentiation of neurosecretory-like cells

Abstract: The structure and regeneration of the digestive system in the crinoid Himerometra robustipinna (Carpenter, 1881) were studied. The gut comprises a spiral tube forming radial lateral processes, which gives it a five-lobed shape. The digestive tube consists of three segments: esophagus, intestine, and rectum. The epithelia of these segments have different cell compositions. Regeneration of the gut after autotomy of the visceral mass progresses very rapidly. Within 6 h after autotomy, an aggregation consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 66 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…Our assumptions about the activation of regenerative processes is supported by an overlap of injury-responsive proteins with those involved in regeneration in sea cucumbers, namely β-microseminoprotein, serum amyloid A, and ependymin-like and avidin-like proteins. Observed associations of cancer-related terms with such proteins as WAPL, LYSTARs, GRAN, BMSP, CATB, CLTR and ENDL is not surprising, because carcinogenesis involves both cell migration and transdifferentiation, which are thought to be important mechanisms of regeneration in echinoderms (Kalacheva et al, 2017). Therefore, our dataset may represent an important tool for discovery of novel proteins involved in regeneration in echinoderms, suggesting important targets for future studies.…”
Section: Discussionmentioning
confidence: 70%
“…Our assumptions about the activation of regenerative processes is supported by an overlap of injury-responsive proteins with those involved in regeneration in sea cucumbers, namely β-microseminoprotein, serum amyloid A, and ependymin-like and avidin-like proteins. Observed associations of cancer-related terms with such proteins as WAPL, LYSTARs, GRAN, BMSP, CATB, CLTR and ENDL is not surprising, because carcinogenesis involves both cell migration and transdifferentiation, which are thought to be important mechanisms of regeneration in echinoderms (Kalacheva et al, 2017). Therefore, our dataset may represent an important tool for discovery of novel proteins involved in regeneration in echinoderms, suggesting important targets for future studies.…”
Section: Discussionmentioning
confidence: 70%
“…variabilis . This type of transdifferentiation is well known in some animals (Becker & Jarriault, ), for example, during transdifferentiation of fibroblasts into neuronal cells (Fishman et al, ), or juxtaligamental cells into enterocytes in Crinoidea (Kalacheva et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…In this case, this transdifferentiation occurs through the direct conversion of exopinacocytes into porocytes without the requirement for cell division. This type of transdifferentiation is well known in animals (Becker & Jarriault, 2016) for example, during transdifferentiation of fibroblasts into neuronal cells (Fishman et al, 2015), or juxtaligamental cells into enterocytes in Crinoidea (Kalacheva, Eliseikina, Frolova, & Dolmatov, 2017).…”
Section: Stage Iii-transformation Of the Regenerative Membrane Intomentioning
confidence: 93%
“…However, in the invertebrate roundworm Caenorhabditis elegans, it was demonstrated that two speci c non-endoderm cell lineages, can be arti cially converted into intestinal cells, which are normally of endoderm origin 3,4 . It remains unclear whether in vivo intergerm layer lineage conversion is unique to these cell types or to this and other invertebrates 5 . The ability to directly reprogram a differentiated vertebrate cell identity in vivo, without spatial or lineage limitations, would indicate that the developmental origin of a cell and its natural microenvironment does not absolutely limit its potential identity, challenging the dogma of in vivo developmental lineage restriction and opening potential new avenues for regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%